Prognostic factors in Polish patients with BRCA1-dependent ovarian cancer - Szatkowski, Wiktor (Hered Cancer Clin Pract, 2016)
BACKGROUND: Treatment outcomes appear to be better for ovarian cancer (OC) patients carrying the BRCA1/2 germline mutation than for patients with sporadic OC. However, most published data are for North American, British and Jewish populations. There have been very few studies on treatment outcomes in Central and Eastern European patients with OC. The aim of this study was to analyse prognostic factors in Polish patients with BRCA1-dependent OC (BRCA1-OC). METHODS: The records of patients with OC treated with surgery and chemotherapy at the Centre of Oncology in Kraków, Poland, between 2004 and 2009 were reviewed. Based on family history, a group of 249 consecutive patients fulfilling the criteria for risk of hereditary OC were selected and tested for the germline BRCA1 mutation. Response to combination therapy (surgery and chemotherapy) in the BRCA1-OC group was assessed based on clinical examination, imaging and serum CA125. RESULTS: Germline BRCA1 mutations were detected in 69 of the 249 patients, but three of these patients failed to complete the study. Finally, 66 patients with BRCA1-OC were included in the study group. The median age of the study patients was 49.5 years. All had undergone primary or interval cytoreductive surgery and chemotherapy. Progression occurred in 48 (72.7 %) of the 66 patients and median time to progression was 20 months. The 5-year overall survival rate in was 43.9 % and median survival time was 32.3 months. On multivariate analysis, the endometrial subtype of OC and serum CA125 < 12.5 U/ml at the end of treatment were independent, positive prognostic factors for 5-year overall survival. CONCLUSION: Prognostic factors for favourable treatment outcomes in Polish patients with BRCA1-OC do not appear to differ from those in patients with sporadic OC. The incidence of the endometrial subtype of OC was relatively high (34.9 %) among women in the study. This was unexpected and has not been reported previously. This subtype of OC was an independent prognostic factor for favourable treatment outcomes.